An Unusual Erupted Complex Composite Odontoma: A Rare Case - Dawasaz Ali Azhar; Mohammad Zahir Kota; Sherif El-Nagdy (Case Reports in Dentistry)
Odontomas are malformations of the dental tissues and may interfere with the eruption of the associated tooth. Complex composite odontoma (CO) was described as a distinct entity for the first time by Broca in 1866. This lesion takes place due to the developmental disturbances where the dental components are laid down in a disorganized manner, due to failure of normal morphodifferentiation. Very few cases of erupted complex composite odontomas have been reported in the literature. The case reported here is of an odontoma found in the left mandibular body, associated with an impacted second molar of a 17-year-old Saudi male. Under local anesthesia the odontoma was surgically removed. Histopathological examination confirmed the diagnosis of CO. The impacted second molar which was left in the mandibular body erupted clinically after 6 months. Erupted CO is rarely seen in the mandibular left body. The early diagnosis, followed by a proper treatment at the right time, will result in a favorable prognosis.